Utilizing Monopoly Game Media to Enhance Students' Motivation Acquisition about the Fulfillment of Balanced Nutrition - Firnaliza Rizona; Fuji Rahmawati; Sigit Purwanto; Rijal Akbar Difa Padiana (GLOBAL HEALTH SCIENCE GROUP, 2025)
The limited knowledge and motivation of balanced nutrition among school children poses a significant challenge to their health and overall development. Inadequate motivation in fulfillmnet of balanced nutrition among school children contributes significantly to the triple burden of malnutrition, encompassing undernutrition, micronutrient deficiencies, and overnutrition. One such approach is the use of interactive educational tools, such as monopoly-based games, which combine learning with play to effectively enhance motivation retention. This study examines the potential of a monopoly game as a health education tool to improve students' understanding and motivation the fulfillment of balanced nutrition. This study was quantitative research which used pre-experimental with one group pre posttest design. A total of 30 students participated in the study, selected through purposive sampling. A pre-test and post-test design was employed to measure the motivation level before and after the intervention. Statistical analysis using the Wilcoxon test revealed a significant improvement in students' motivation, with a p-value of 0.000 (p < 0.05), indicating the effectiveness of the intervention by using monopoly games about balanced nutrition. Implementing educational media through games, such as the monopoly game, significantly enhances students' motivation in fulfillment of balanced nutrition.